Contextualization as a Teaching Strategy in Chemistry Video Lessons - Fidelis, J. P. S. [UNESP]; Gibin, G. B. [UNESP] (Brazilian Chemical Soc, 2016)
This study analyzed ninety Chemistry video lessons available on youtube.com.br site during the period of one year, in order to quantify the use of context in these classes. Furthermore, it was also made a classification of the observed contexts based on Kato and Kawasaki (2011) and Smith et al. (2010). For the selection of videos, videos that were analyzed showed up ten thousand views, since it consists of an indication of the use of this resource by students. After the analysis it was established a superficial use of contextualization as a teaching strategy, and it was observed that there is a field of traditional teaching approach, with definitions of concepts and / or phenomena, using examples and problem solving.
Keywords: Video lessons; Contextualization; didactic strategy